A circularly polarized folded reflectarray antenna using a polarization-sensitive linear-to-circular polarization converter - Liu, Shuang; Li, Yin; Wong, Sai-Wai; Zhang, Xiao; Wang, Shiyan; Fang, Liang; Gao, Qiang (Frontiers in Physics, 2022)
A low-profile circularly polarized folded reflectarray antenna(CPFRA) is proposed in this work. Compared with traditional CPFRA that consist of a main reflectarray, a polarization grid (PG), and a linear-to-circular polarization (LP-CP) converter, the proposed CPFRA utilize a polarization-sensitive LP-CP converter, which plays both of the roles of PG and LP-CP converter, to minimize the profile of the CPFRA. One period of the polarization-sensitive LP-CP converter consists of a LP and a CP patch on the bottom and top layer of the substrates respectively, which are connected to each other by a metalized via. Due to its frequency selective characteristic, the polarization-sensitive LP-CP surface can simultaneously reflect the x-polarized waves and transfer the received y-polarized waves into CP state. A 1-bit unit cell at the bottom layer is adopted for polarization conversion and phase shift. A planar patch antenna is integrated as the primary feeding source. A high-gain circularly polarized folded reflectarray antenna at X-band is designed, fabricated, and measured. Both simulated and measured results show the proposed CPFRA has both the advantages of high-gain and lower profile over its triditional counter parts.